Slow-release scale-inhibiting filler as well as preparation method and application thereof

The slow-release anti-scaling filler addresses issues of adhesion and stability by using a coated inorganic filler with adsorbed antiscalant groups, ensuring sustained scale inhibition and coating compatibility.

CN119242095APending Publication Date: 2025-01-03SHANDONG DONGHONG PIPE IND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411300870.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing scale inhibitors used in coatings react with active groups, affecting adhesion, environmental stability, coating properties, dispersion stability, and chemical stability, leading to reduced durability and performance.

Method used

A slow-release anti-scaling filler composed of inorganic filler, antiscalant, and coating film, where polar groups of the antiscalant are adsorbed through hydrogen bonding or electrostatic forces, and wrapped with a coating membrane to prevent direct contact, ensuring slow release and compatibility with coatings.

Benefits of technology

The slow-release filler maintains effective scale inhibition while preserving coating performance and stability, allowing for industrial application without adverse effects on adhesion, environmental stability, or chemical susceptibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242095A_ABST
    Figure CN119242095A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of slow-release scale-inhibiting fillers, and particularly relates to a slow-release scale-inhibiting filler as well as a preparation method and application thereof. The preparation method comprises the following steps: uniformly mixing and dispersing an inorganic filler, a scale inhibitor and a solvent, and carrying out rotary evaporation until the solvent is completely volatilized to prepare an intermediate; uniformly mixing the intermediate, the coating film and a solvent, and performing rotary evaporation until the solvent is completely volatilized to prepare an intermediate containing the coating film; and treating the intermediate containing the coating film through jet milling to obtain the slow-release scale-inhibiting filler. The scale inhibitor has the advantages that the scale inhibition function can be realized, the validity period can be prolonged, the concentration can be regulated and controlled, and the scale inhibitor can be used as a slow-release scale inhibitor and also can be matched with various coating systems. The preparation method is simple and convenient, industrial production is easy, the scale inhibitor loading capacity is ideal, the safety is good, the scale inhibitor can be selected or compounded according to needs, and the wrapping film is green and pollution-free.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of slow-release anti-scaling fillers, and in particular relates to a slow-release anti-scaling filler and a preparation method and application thereof. Background Art

[0002] The application of scale inhibitors in water-using industries such as steel and petrochemicals has become mature, and can be roughly divided into three categories: the first is natural polymer scale inhibitors, such as tannins and gallic acid. These scale inhibitors are widely available and easy to extract. With their own characteristics, they can react with Ca 2+ Mg 2+ The combined functional groups can capture calcium and magnesium ions to form chelates, which rely on the dual methods of chelation solubilization and lattice distortion to inhibit the formation of scale and ultimately achieve good scale inhibition effects. The second is phosphorus-containing scale inhibitors, such as 2-hydroxyphosphonoacetic acid, aminotrimethylenephosphonic acid, etc.; the CP bond in its molecular structure is quite stable, rich in numerous carboxyl and phosphonic acid ligands, and can bind to Ca 2+ Mg 2+ Combined to form a five-membered ring coordination compound, thus forming a chelate, which reduces the generation of scale by means of chelation solubilization and lattice distortion. The third is a new type of green and environmentally friendly scale inhibitor, represented by green biodegradable scale inhibitors such as polyaspartic acid (PASA) and polyepoxysuccinic acid (PESA). PASA is a polyamino acid with an amide bond structure, which can effectively inhibit common calcium scale and is easily biodegradable. However, the above three types of scale inhibitors themselves contain a large number of active groups. Since the active groups will react with some additives in the coating, the performance of the coating will be greatly reduced, and it may even fail to solidify, and cannot be directly used in the coating industry.

[0003] The Chinese invention patent with publication number CN 106497326 A adds anti-scaling functional fillers to the coating components. The anti-scaling coating prepared avoids the various disadvantages caused by adding anti-scaling agents alone and provides a continuous and stable anti-scaling effect. However, the anti-scaling functional fillers used include porous materials, acidic anti-scaling agents and salt anti-scaling agents, but no encapsulation film is set on the surface of the filler, that is, the anti-scaling agent can be in direct contact with the coating system. There are the following problems: (1) Negative impact on adhesion: Although polar groups help to enhance adhesion, they may have a negative impact on adhesion in some cases. For example, polar groups may increase the polarity of the coating, which is not conducive to improving adhesion when attached to non-polar substrates; (2) Environmental stability issues: The introduction of polar groups may affect the environmental stability of the coating. Polar groups may make the coating more susceptible to moisture absorption or the effects of certain chemicals, thereby reducing the durability of the coating; (3) Changes in coating properties: The introduction of polar groups may change the rheological properties and drying characteristics of the coating, which may affect the coating's construction performance and the final coating quality; (4) Coating dispersion stability issues: In high-solid coating systems, the introduction of polar groups may affect the dispersion stability of the coating. The selection and design of dispersants need to consider the interaction between polar groups and pigments and resins to ensure good dispersion and coating stability; (5) Chemical stability issues: Polar groups may make coatings more susceptible to chemical attack, especially in industrial environments, which may shorten the service life of the coating. Summary of the invention

[0004] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a slow-release anti-scaling filler and a preparation method and application thereof.

[0005] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0006] In a first aspect, the present invention provides a slow-release anti-scaling filler composition, which is composed of the following components in parts by weight:

[0007] Inorganic filler: 1 to 10 parts

[0008] Antiscalant: 1 to 10 parts

[0009] Coating film: 1 to 10 parts

[0010] Solvent: 1 to 10 parts;

[0011] Wherein, the polar groups contained in the scale inhibitor are adsorbed to the surface of the inorganic filler through hydrogen bonding, electrostatic or van der Waals forces;

[0012] The polar group is one or more of a carboxyl group, a hydroxyl group or a phosphonic acid group.

[0013] In some other embodiments of the present invention, the scale inhibitor is one or more of polyaspartic acid, polyepoxysuccinic acid, tannic acid, gallic acid, 2-hydroxyphosphonoacetic acid or aminotrimethylenephosphonic acid;

[0014] In some other embodiments of the present invention, the coating membrane is one or more of natural phospholipids, polyethylene glycol-polylactic acid, polyethylene glycol-polycaprolactone, phospholipid-cholesterol, Tween, and Span-20;

[0015] Preferably, the natural phospholipid is soybean lecithin or egg yolk lecithin.

[0016] In some other embodiments of the present invention, the filler is one or more of nano-SiO2, fruit shell nano-activated carbon, coconut shell nano-activated carbon, coal columnar nano-activated carbon or nano-molecular sieve;

[0017] Or, the solvent is one or more of water, ethanol, ethyl acetate, methanol, dichloromethane, and acetone.

[0018] In some other embodiments of the present invention, the following components are included in parts by weight:

[0019] Inorganic filler: 2-10 parts

[0020] Antiscalant: 1-10 parts

[0021] Coating film: 1 -2 parts

[0022] Solvent: 1-2 parts.

[0023] In a second aspect, the present invention provides a method for preparing a slow-release anti-scaling filler, comprising the following steps:

[0024] S1, preparing the slow-release antiscaling filler composition described in the first method, mixing and dispersing the inorganic filler, antiscaling agent and solvent uniformly, and rotary evaporating until the solvent is completely evaporated to obtain an intermediate;

[0025] S2, after the intermediate, the coating film and the solvent are uniformly mixed, rotary evaporation is performed until the solvent is completely evaporated to obtain the intermediate containing the coating film;

[0026] S3, treating the intermediate containing the coating film by air jet milling to obtain a slow-release antiscaling filler.

[0027] In some other embodiments of the present invention, in step S1, the concentration of the antiscalant is 5-10wt.%;

[0028] The rotary evaporation conditions are: continuous evaporation reaction at 50-80°C and a relative pressure of -0.2 MPa for 1-4 hours.

[0029] In some other embodiments of the present invention, in step S2, the concentration of the coating film is 5-10wt.%; preferably, the concentration of the coating film is 10wt.%;

[0030] The rotary evaporation conditions are: continuous evaporation reaction at 40-60° C. and a relative pressure of −0.2 MPa for 1-6 hours.

[0031] In some other embodiments of the present invention, in step S3, the conditions of the jet mill treatment are: gas pressure of 0.7-0.9 MPa, feed rate of 5-10 kg / h, and classifier wheel speed of 6000-8000 rpm;

[0032] The particle size of the obtained slow-release anti-scaling filler is above 3000 meshes.

[0033] In a third aspect, the present invention provides the use of the slow-release anti-scaling filler described in the first aspect in a coating, wherein the coating is a water-based or oil-based coating.

[0034] The beneficial effects achieved by one or more technical solutions of the present invention are as follows:

[0035] (1) The slow-release anti-scaling filler provided by the present invention utilizes the porous adsorption principle of inorganic fillers such as SiO2, nano-activated carbon, and nano-molecular sieves to compound with anti-scaling agents; the anti-scaling agents can be selected from organic phosphonic acid anti-scaling agents, natural polymer anti-scaling agents, new green anti-scaling agents, or a combination thereof according to the specific needs of the industry. The molecular structure of the anti-scaling agent contains polar groups such as carboxyl, hydroxyl, and phosphonic acid groups, which can interact and tightly bind with the functional groups on the surface of the nano-inorganic filler through hydrogen bonding, electrostatic effects, van der Waals forces, and the like. In addition, the surface is wrapped with a coating film to achieve the goal of being harmless to the human body and green and pollution-free.

[0036] (2) The preparation method of the present invention is simple and easy to realize industrial-scale production. The scale inhibitor loading amount is ideal, and the release concentration of the scale inhibitor can be adjusted according to the dosage ratio, and the safety performance is excellent.

[0037] (3) The slow-release anti-scaling filler of the present invention can be applied to the coating industry. The slow-release anti-scaling filler is coated with a drug carrier. The active groups of the anti-scaling agent are released only after the surface layer disintegrates, thereby avoiding the reaction of the anti-scaling agent in the coating system. The coating film controls the release. When used, the anti-scaling agent is coated and the active groups are released only after the surface layer disintegrates, thereby achieving slow-release anti-scaling and ensuring the coating performance. Therefore, the invention is of great significance in the industrial application of anti-scaling. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The slow-release effect diagram of the slow-release anti-scaling filler prepared in Example 1 of the present invention and Comparative Examples 1-4;

[0039] Figure 2 This is a scale inhibition effect diagram of the slow-release scale inhibition filler prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0040] The following embodiments are given to further illustrate the present invention in detail. It should be pointed out that the following embodiments cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by engineers and technicians in this field based on the above-mentioned invention content still fall within the scope of protection of the present invention.

[0041] Example 1

[0042] S1, weighing 2 parts of nano-SiO2 and 10 parts of ethanol solution containing 5wt.% of 2-hydroxyphosphonoacetic acid (HPAA), mixing, and ultrasonically dispersing for 5-10 minutes to form a uniformly mixed dispersion; transferring the dispersion to a round-bottom flask, using a rotary evaporator at 50°C and a relative pressure of -0.2MPa, continuously evaporating for 1-3h until the solvent is completely volatilized, to obtain a SiO2 / HPAA intermediate.

[0043] S2, take 1 part of SiO2 / HPAA intermediate and mix it with 10 parts of ethyl acetate solution containing 10wt.% of soybean lecithin, ultrasonically disperse it for 5-10 minutes, move it to a round-bottom flask, and then transfer it to a rotary evaporator at 50°C and a relative pressure of -0.2MPa, and evaporate it continuously for 1-6h until the solvent is completely volatilized to form an intermediate containing a coating film.

[0044] S3, treating the intermediate containing the coating film by airflow milling to prepare a slow-release anti-scaling filler with a particle size of 3000 mesh. The conditions of the airflow milling treatment are: gas pressure of 0.7-0.9 MPa, feed rate of 5-10 kg / h, and classification wheel speed of 6000-8000 rpm. The mass ratio of Lecithin / SiO2 / HPAA in the obtained slow-release anti-scaling filler is 2:4:1.

[0045] The prepared slow-release anti-scaling filler was placed in a beaker of 500 mL of deionized water, and the pH value of the solution was measured every 10 hours to test the slow-release effect of the slow-release anti-scaling filler. Figure 1 This is a slow-release effect diagram of the prepared slow-release scale inhibitor filler. As the coating film disintegrates, the corrosion inhibitor is released, making the solution acidic. By testing the pH value of the solution, the slow-release function of the filler can be proved.

[0046] The scale inhibition rate was tested according to standard SY / T 5673-2020. The results are as follows: Figure 2 It can be seen that the scale inhibition rate of the slow-release scale-inhibiting filler prepared by the present invention does not change much over time, and is maintained at 85-90% within 0-150 hours.

[0047] Example 2

[0048] S1, weigh 10 parts of nano-SiO2 and 10 parts of an aqueous solution containing 10wt.% polyaspartic acid (PASP), mix them, and ultrasonically disperse them for 5 to 10 minutes to form a uniformly mixed dispersion; transfer the dispersion to a round-bottom flask, and use a rotary evaporator to evaporate continuously for 1 to 3 hours at 50°C and a relative pressure of -0.2MPa until the solvent is completely volatilized to obtain a SiO2 / PASP intermediate.

[0049] S2, take 1 part of SiO2 / PASP intermediate and 1 part of ethyl acetate solution containing 10wt.% of soybean lecithin, mix them, ultrasonically disperse them for 5 to 10 minutes, then transfer them to a round-bottom flask, and use a rotary evaporator to evaporate continuously for 1 to 6 hours at 40°C and a relative pressure of -0.2MPa until the solvent is completely evaporated to form an intermediate containing a coating film.

[0050] S3, treating the intermediate containing the coating film by air jet milling to prepare a slow-release anti-scaling filler with a particle size of 3000 mesh. The conditions of the air jet milling treatment are the same as those in Example 1.

[0051] Example 3

[0052] S1, weighing 10 parts of nano-activated carbon (AC) and 5 parts of an aqueous solution containing 20wt.% polyepoxysuccinic acid (PESA), mixing them, and ultrasonically dispersing them for 5 to 10 minutes to form a uniformly mixed dispersion; transferring the dispersion to a round-bottom flask, and using a rotary evaporator at 60°C and a relative pressure of -0.2MPa, continuously evaporating for 1 to 3 hours until the solvent is completely volatilized, to obtain an AC / PASP intermediate.

[0053] S2, taking 1 part of AC / PASP intermediate and 1 part of chloroform solution containing 10wt% egg yolk phospholipids, mixing, ultrasonically dispersing for 5-10 minutes, then transferring to a round-bottom flask, using a rotary evaporator at 50°C and a relative pressure of -0.2MPa, continuously evaporating for 1-6 hours until the solvent is completely volatilized, to form an intermediate containing a coating film

[0054] S3, treating the intermediate containing the coating film by air jet milling to prepare a slow-release anti-scaling filler with a particle size of 3000 mesh. The conditions of the air jet milling treatment are the same as those in Example 1.

[0055] Example 4

[0056] S1, weigh 10 parts of nano-SiO2 and 1 part of an aqueous solution containing 50wt% polyepoxysuccinic acid (PESA), mix them, and ultrasonically disperse them for 5 to 10 minutes to form a uniformly mixed dispersion; transfer the dispersion to a round-bottom flask, and use a rotary evaporator to evaporate continuously for 1 to 3 hours at 70°C and a relative pressure of -0.2MPa until the solvent is completely evaporated to obtain a SiO2 / PASP intermediate.

[0057] S2, take 1 part of SiO2 / PASP intermediate and mix it with 2 parts of dichloromethane solution containing 10wt% polyethylene glycol-polylactic acid (PEG-PLA), ultrasonically disperse it for 5 to 10 minutes, and then transfer it to a round-bottom flask. Use a rotary evaporator at 60°C and a relative pressure of -0.2MPa to continuously evaporate for 1 to 6 hours until the solvent is completely evaporated to form an intermediate containing a coating film.

[0058] S3, treating the intermediate containing the coating film by air jet milling to prepare a slow-release anti-scaling filler with a particle size of 3000 mesh. The conditions of the air jet milling treatment are the same as those in Example 1.

[0059] Example 5

[0060] S1, weigh 10 parts of nano-SiO2 and 10 parts of 5wt% tannic acid (TA) aqueous solution, mix them, and ultrasonically disperse them for 5-10 minutes to form a uniformly mixed dispersion; transfer the dispersion to a round-bottom flask, and use a rotary evaporator to evaporate continuously for 1-3 hours at 80°C and a relative pressure of -0.2MPa until the solvent is completely volatilized to obtain a SiO2 / TA intermediate.

[0061] S2, take 1 part of SiO2 / TA intermediate and 2 parts of 10wt% polyethylene glycol-polycaprolactone dichloromethane solution, ultrasonically disperse for 5 to 10 minutes, then transfer to a round-bottom flask, use a rotary evaporator at 50°C and a relative pressure of -0.2MPa, and evaporate continuously for 1 to 6 hours until the solvent is completely evaporated; forming an intermediate containing a coating film.

[0062] S3, treating the intermediate containing the coating film by air jet milling to prepare a slow-release anti-scaling filler with a particle size of 3000 mesh. The conditions of the air jet milling treatment are the same as those in Example 1.

[0063] Example 6

[0064] S1, weigh 2.5 parts of nano-SiO2 and 10 parts of ethanol solution containing 5wt.% gallic acid (GA), ultrasonically disperse for 5-10 minutes to form a uniformly mixed dispersion; transfer the dispersion to a round-bottom flask, use a rotary evaporator at 90°C and a relative pressure of -0.2MPa, and evaporate continuously for 1-3h until the solvent is completely volatilized to obtain a SiO2 / GA intermediate.

[0065] S2, take 1 part of SiO2 / GA intermediate and 1 part of 10wt% phospholipid-cholesterol chloroform solution, mix them, ultrasonically disperse them for 5 to 10 minutes, then transfer them to a round-bottom flask, and use a rotary evaporator at 60°C and a relative pressure of -0.2MPa to continuously evaporate for 1 to 6 hours until the solvent is completely evaporated to form an intermediate containing a coating film.

[0066] S3, treating the intermediate containing the coating film by air jet milling to prepare a slow-release anti-scaling filler with a particle size of 3000 mesh. The conditions of the air jet milling treatment are the same as those in Example 1.

[0067] Example 7

[0068] S1, weigh 2 parts of nano-SiO2 and 10 parts of ethanol solution containing 5wt% 2-hydroxyphosphonoacetic acid (HPAA), mix them, and ultrasonically disperse them for 5-10 minutes to form a uniformly mixed dispersion; transfer the dispersion to a round-bottom flask, and use a rotary evaporator to evaporate continuously for 1-3 hours at 50°C and a relative pressure of -0.2MPa until the solvent is completely volatilized to obtain a SiO2 / HPAA intermediate.

[0069] S2, take 1 part of SiO2 / HPAA intermediate and mix it with 2 parts of ethanol solution containing 10wt.% Span-20, ultrasonically disperse it for 5-10 minutes, then transfer it to a round-bottom flask, and use a rotary evaporator to evaporate continuously for 1-6 hours at 80°C and a relative pressure of -0.2MPa until the solvent is completely evaporated to form an intermediate containing a coating film.

[0070] S3, treating the intermediate containing the coating film by air jet milling to prepare a slow-release anti-scaling filler with a particle size of 3000 mesh. The conditions of the air jet milling treatment are the same as those in Example 1.

[0071] Example 8

[0072] S1, weigh 2 parts of nano-SiO2 and mix with 10 parts of an aqueous solution containing 5wt% aminotrimethylenephosphonic acid (ATMP), and disperse them by ultrasonic for 5 to 10 minutes to form a uniformly mixed dispersion; transfer the dispersion to a round-bottom flask, and use a rotary evaporator to evaporate continuously for 1 to 3 hours at 50°C and a relative pressure of -0.2MPa until the solvent is completely volatilized to obtain a SiO2 / ATMP intermediate.

[0073] S2, take 1 part of SiO2 / ATMP intermediate and mix it with 2 parts of 10wt% lecithin ethanol solution, ultrasonically disperse it for 5 to 10 minutes, then transfer it to a round-bottom flask, and use a rotary evaporator at 50°C and a relative pressure of -0.2MPa to continuously evaporate for 1 to 6 hours until the solvent is completely evaporated to form an intermediate containing a coating film.

[0074] S3, treating the intermediate containing the coating film by air jet milling to prepare a slow-release anti-scaling filler with a particle size of 3000 mesh. The conditions of the air jet milling treatment are the same as those in Example 1.

[0075] Comparative Example 1

[0076] The difference from Example 1 is that step S2 is omitted, the SiO2 / HPAA intermediate is subjected to airflow milling, and the other conditions are the same as those of Example 1. The mass ratio of SiO2 / HPAA in the obtained slow-release anti-scaling filler is 4:1.

[0077] Comparative Example 2

[0078] The difference from Example 1 is that in step S1, 2 parts of nano-SiO2 are weighed and mixed with 10 parts of ethanol solution containing 10 wt.% of 2-hydroxyphosphonoacetic acid (HPAA);

[0079] In step S2, 1 part of SiO2 / HPAA intermediate is mixed with 10 parts of ethyl acetate solution containing 5 wt.% soybean lecithin; other conditions are the same as those in Example 1. The mass ratio of Lecithin / SiO2 / HPAA in the obtained slow-release anti-scaling filler is 1:4:2.

[0080] Comparative Example 3

[0081] The difference from Example 1 is that in step S2, 1 part of SiO2 / HPAA intermediate is mixed with 10 parts of ethyl acetate solution containing 5 wt.% soybean lecithin, and the other conditions are the same as those in Example 1. The mass ratio of Lecithin / SiO2 / HPAA in the obtained slow-release anti-scaling filler is 1:4:1.

[0082] Comparative Example 4

[0083] The difference from Example 1 is that in step S1, 2 parts of nano-SiO2 are weighed and mixed with 10 parts of ethanol solution containing 10 wt.% of 2-hydroxyphosphonoacetic acid (HPAA), and the other conditions are the same as those in Example 1.

[0084] The mass ratio of Lecithin / SiO2 / HPAA in the prepared slow-release scale-inhibiting filler is 2:4:2.

[0085] The slow-release anti-scaling fillers prepared in Comparative Examples 1-4 were placed in a beaker of 500 mL of deionized water, and the pH value of the solution was measured every 10 hours to test the slow-release effect of the slow-release anti-scaling fillers.

[0086] Figure 1 The slow-release effect diagram of the slow-release scale-inhibiting filler prepared in Examples 1-4. As the coating film disintegrates, the corrosion inhibitor is released, which makes the solution acidic. By testing the pH value of the solution, the slow-release function of the filler can be proved. It can be seen that in Example 1, since no coating film is added, the filler is quickly released within 20 hours, and the slow-release function is poor; from the test data of Examples 2-4, it can be seen that the slow-release performance is related to the content of the scale inhibitor and the coating agent, and the more the coating agent content, the better the slow-release function.

[0087] Comparative Example 5

[0088] Different from Example 1, no scale inhibitor was added, 2 parts of nano-SiO2 were directly weighed and mixed with 10 parts of ethyl acetate solution containing 10 wt.% of soybean lecithin, ultrasonically dispersed for 5 to 10 minutes, transferred to a round-bottom flask, and then transferred to a rotary evaporator at 50°C and a relative pressure of -0.2MPa, and evaporated continuously for 1 to 6 hours until the solvent was completely volatilized, and then treated by jet milling to prepare a slow-release scale inhibitor filler with a particle size of 3000 meshes, and other conditions were the same as in Example 1. The obtained filler composition was Lecithin / SiO2.

[0089] Table 1 below shows the pH and scale inhibition performance of the slow-release scale inhibition fillers prepared in the examples of the present invention and the comparative examples measured after 100 hours.

[0090] Table 1 pH and scale inhibition performance of slow-release scale inhibition filler measured after 100 hours

[0091]

[0092]

[0093] It can be seen from the results in Table 1 that the performance of the slow-release anti-scaling filler obtained in Examples 1-8 is better than that in Comparative Examples 1-5.

[0094] The fillers prepared in Examples 1-8 and Comparative Examples 1-5 were added to a water-based epoxy resin coating system (F0704 (water-based epoxy resin) + F0705 (water-based epoxy resin curing agent), Yoshida Chemical) and an oily polyurethane coating system (single-component polyurethane waterproof coating system, Shouguang Lufeng Waterproof Materials Co., Ltd.) to make a 50*100*1mm sample plate, which was then placed in a 0.01mol / LCaCl2, 0.01mol / LNaHCO3 aqueous solution and immersed for 24h at 70°C and 1000r / min for testing.

[0095] The reference examples are a water-based epoxy resin coating system without adding fillers (F0704 (water-based epoxy resin) + F0705 (water-based epoxy resin curing agent), Yoshida Chemical) and an oily polyurethane coating system (one-component polyurethane waterproof coating system, Shouguang Lufeng Waterproof Materials Co., Ltd.).

[0096] The test results are shown in Table 2.

[0097] Table 2 Performance of slow-release anti-scaling filler in coating system

[0098]

[0099]

[0100] As can be seen from Table 2, the slow-release anti-scaling filler prepared in the embodiment of the present invention is significantly better than the comparative example and the reference example in the coating system performance. The reason for the pinholes in comparative example 1 is briefly analyzed as follows: Chemical incompatibility: The scale inhibitor may react chemically with certain additives in the waterborne epoxy system to produce insoluble substances, gases or change the surface tension of the coating, thereby causing the formation of pinholes. Surface tension change: The reaction may change the surface tension of the coating, so that the coating cannot be evenly spread and leveled during the drying process, and pinholes are easily formed. Bubble generation: The reaction may produce bubbles, and during the drying process of the coating, the bubbles burst and leave pinholes. This shows that the scale-inhibiting slow-release filler prepared by the present invention can not only realize the function of scale inhibition itself, but also prolong the effective period and adjust the concentration without affecting the performance of the coating. It can be used as a slow-release anti-scaling agent and can also be compatible with a variety of coating systems. The preparation method is simple and easy to industrialize. The scale inhibitor loading amount is ideal and safe. The scale inhibitor can be selected or compounded as needed, and the wrapping film is green and pollution-free.

Claims

1. A slow-release anti-scaling filler, characterized in that: By weight, it is composed of the following components: Inorganic filler: 1 to 10 parts Antiscalant: 1 to 10 parts Coating film: 1 to 10 parts Solvent: 1 to 10 parts; Wherein, the polar groups contained in the scale inhibitor are adsorbed to the surface of the inorganic filler through hydrogen bonding, electrostatic or van der Waals forces; The polar group is one or more of a carboxyl group, a hydroxyl group or a phosphonic acid group.

2. The slow-release anti-scaling filler according to claim 1, characterized in that: The scale inhibitor is one or more of polyaspartic acid, polyepoxysuccinic acid, tannic acid, gallic acid, 2-hydroxyphosphonoacetic acid or aminotrimethylenephosphonic acid.

3. The slow-release anti-scaling filler according to claim 1, characterized in that: The coating film is one or more of natural phospholipids, polyethylene glycol-polylactic acid, polyethylene glycol-polycaprolactone, phospholipid-cholesterol, Tween, and Span-20; Preferably, the natural phospholipid is soybean lecithin or egg yolk lecithin.

4. The slow-release anti-scaling filler according to claim 1, characterized in that: The filler is one or more of nano-SiO2, fruit shell nano-activated carbon, coconut shell nano-activated carbon, coal columnar nano-activated carbon or nano-molecular sieve; Or, the solvent is one or more of water, ethanol, ethyl acetate, methanol, dichloromethane, and acetone.

5. The slow-release anti-scaling filler according to claim 1, characterized in that: By weight, it includes the following components: Inorganic filler: 2-10 parts Antiscalant: 1-10 parts Coating film: 1-2 copies Solvent: 1-2 parts.

6. A method for preparing a slow-release anti-scaling filler, characterized in that: The following steps are involved: S1, preparing the slow-release anti-scaling filler according to any one of claims 1 to 5, mixing and dispersing the inorganic filler, anti-scaling agent and solvent uniformly, and rotary evaporating until the solvent is completely evaporated to obtain an intermediate; S2, after the intermediate, the coating film and the solvent are uniformly mixed, rotary evaporation is performed until the solvent is completely evaporated to obtain the intermediate containing the coating film; S3, treating the intermediate containing the coating film by air jet milling to obtain a slow-release antiscaling filler.

7. The preparation method according to claim 6, characterized in that: In step S1, the concentration of the scale inhibitor is 5-10wt.%; The rotary evaporation conditions are: continuous evaporation reaction at 50-80°C and a relative pressure of -0.2 MPa for 1-4 hours.

8. The preparation method according to claim 6, characterized in that: In step S2, the concentration of the coating film is 5-10wt.%; preferably, the concentration of the coating film is 10wt.%; The rotary evaporation conditions are: continuous evaporation reaction at 40-60° C. and a relative pressure of −0.2 MPa for 1-6 hours.

9. The preparation method according to claim 6, characterized in that: In step S3, the conditions of the jet mill treatment are: gas pressure of 0.7-0.9 MPa, feed rate of 5-10 kg / h, and classifier wheel speed of 6000-8000 rpm; The particle size of the obtained slow-release anti-scaling filler is above 3000 meshes.

10. Use of the slow-release anti-scaling filler according to any one of claims 1 to 5 in coatings, characterized in that: The coating is water-based or oil-based coating.